2009
DOI: 10.5539/elt.v2n2p98
|View full text |Cite
|
Sign up to set email alerts
|

Has Portfolio Assessment Become Common Practice in EFL Classrooms? Empirical Studies from China

Abstract: This paper describes the results of an investigation into the use of portfolio assessment (PA) in Chinese context, beginning with a survey of the rationale for the use of portfolios with students. Then the empirical study is presented and the teacher's and the student's as well as the English teaching advisor's voices are revealed through excerpts collected from the questionnaire and the interviews. The findings show that portfolio assessment is in its infancy. The factors that might have hindered its progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
2
13
1
Order By: Relevance
“…This becomes difficult when considering the workload of teachers, the number of pupils in each class (25)(26)(27)(28)(29)(30), and the long curriculum that teachers need to cover in a limited time. This is consistent with findings from other studies (Yang, 2007;Yu-Ching, 2008;Zhang, 2009;Demir, Ozturk, & Dokeme, 2011;Chroinin & www.ccsenet.org/ies International Education Studies Vol. 7, No.…”
Section: 937 Highsupporting
confidence: 83%
See 1 more Smart Citation
“…This becomes difficult when considering the workload of teachers, the number of pupils in each class (25)(26)(27)(28)(29)(30), and the long curriculum that teachers need to cover in a limited time. This is consistent with findings from other studies (Yang, 2007;Yu-Ching, 2008;Zhang, 2009;Demir, Ozturk, & Dokeme, 2011;Chroinin & www.ccsenet.org/ies International Education Studies Vol. 7, No.…”
Section: 937 Highsupporting
confidence: 83%
“…Similarly, statement 1 reflects teachers' perceptions of their skills and knowledge in their reporting 'always' (67.7%) and 'often' (26.3%). However, this finding is inconsistent with other studies in which teachers were found illiterate in alternative assessment (Mertler & Campell, 2005;Chan, Kennedy, & Fok, 2006;Metin & Demiryurek, 2009;Zhang, 2009;Tangdhanakanond & Wongwanich, 2012). This inconsistency might be attributed to differences in assessment methods used in the different countries.…”
Section: Wwwccsenetorg/iescontrasting
confidence: 56%
“…The student's portfolio is considered as a vehicle that facilitates communication between parents, students and teachers (Zhang, 2009). By compiling portfolios, parents get a chance to know about their children's level and progress over a period of time.…”
Section: The Advantages Of the Student's Portfolio For Teachers And Pmentioning
confidence: 99%
“…Moreover, Caner found that not training students to implement the portfolio would be another obstacle that students would suffer from during the process of implementing the portfolios. Therefore, many researchers stressed on the importance of training students and clarifying the purpose, content and benefits of the portfolio for students (Mok, 2012;Zhang, 2009).…”
Section: Challenges That Students May Face When Implementing the Studmentioning
confidence: 99%
See 1 more Smart Citation